StMYB66, a R2R3-myb Transcription Factor, Regulates Plant Growth and Anthocyanin Accumulation in Potato (Solanum tuberosum L.) - Yu, T.; Wang, D.; Fu, X.; Liu, Z. (2025)
Potatoes are a vital noncereal staple crop that plays a critical role in global food security. Identifying key genes involved in potato growth and development is essential for improving yield and sustainability. In this study, we characterized StMYB66, a potato gene homologous to AtMYB88 and AtMYB124, encoding an R2R3 MYB transcription factor. The full-length open reading frame of StMYB66 is 1413 bp, encoding 470 amino acids. Transgenic lines overexpressing StMYB66 were developments using polymerase chain reaction identification and selection medium cultivation. The highest expression of StMYB66 was observed in sprouting tubers, with significantly increased expression following Phytophthora infestans infection and low nitrogen treatment. Elevated expression levels were also observed in red tubers compared with yellow ones. Overexpression of StMYB66 resulted in shorter plant height, increased root biomass, and purple stem coloration, suggesting its role in anthocyanin accumulation. Comparative transcriptomic analysis between the receipt line (Atlantic) and the overexpression line (OE-T01) revealed that StMYB66 primarily regulates genes involved in cell wall remodeling, influencing cellulose pectin, and lignin biosynthesis, thereby modulating potato growth. These findings demonstrate that StMYB66 is a key regulator of potato growth, anthocyanin biosynthesis, and stress response, making it a promising candidate for potato breeding programs.